RESEARCH OF PHYSICAL AND MECHANICAL PROPERTIES NONWOVEN MATERIALS BASED ON POLYLACTIC ACID - БУЛГАКОВ, Є. С.; ПУШКАРЬОВ, Д. В.; САВЧЕНКО, Б. М.; СОВА, Н. В.; СЛЄПЦОВ, О. О. (Technologies and Engineering, 2024)
Purpose. This article aims to study and compare the physical and mechanical properties of nonwoven materials made of polylactic acid and polypropylene. Methodology. Non-woven polymer materials made of polypropylene and polylactic acid were obtained by the method of aerodynamic spraying of melt on a receiving drum (melt-blown) on a laboratory installation. Physico-mechanical properties such as strength and elongation at break were evaluated using a P-5 tensile machine (according to ISO 5725-1). The rheological characteristics of the studied polymers were evaluated by measuring the melt flow index according to ISO 1133. Findings. The possibility of manufacturing non-woven material from polylactic acid on equipment suitable for polypropylene processing has been experimentally confirmed. The parameters of fiber structure, elongation, and breaking strength were investigated. Polylactic acid non-woven material was found to have 7–30 times higher tensile strength and 7–10 times less elongation at break compared to polypropylene non-woven material in the investigated range of median fiber diameters. Originality. The dependence of the physical and mechanical properties of non-woven materials on the average diameter of elementary fibers was established. Practical value. The technological possibilities of using polylactic acid as a material for the production of non-woven filter materials have been established.